ALIENATION CHANGES IN FORMATION COMMISSION OF INDONESIAN CONSTITUTION OF1945 (Contemplation Towards The Fifth Amendment) - Novendri Mohamad Nggilu; Lisnawaty W Badu; Suwitno Y Imran (UNISSULA, 2018)
The results of the fou rth amendment Constitution of NRI 1945 leaving academic debate, not only in terms of the substance of the constitution that still has weaknesses and needs to be improved and perfected through the fifth amendment of the Constitution of N R I 1945, but also in terms of process changes that lead to refractive mainly against the spirit of Constitutional Commission , Refraction spirit of the Constitutional Commission took place on two points: first, the establishment of the Constitutional Commission which was form ed to have lost momentum, as well as the tasks assigned by the Assembly to the Constitutional Commission so minimalist that is limited to conduct a comprehensive review and was impressed merely fix systematize and writing of the Constitution of NRI 1945 w hich have been produced by the Assembly.